A New Approach to the Modeling of Magnetorheological Dampers and Application to Resonance Control - Letelier-Sotomayor, M; Siginer, D (American Society of Mechanical Engineers, 2021)
A predetermined flow pattern in a magnetorheological damper providing continuously variable resistance to flow is required for efficient damping of a given load. The required predetermined flow pattern rests on the a priori determination of the constitutive properties of the magnetorheological (MR) fluid determined to generate variable resistance to flow. The inverse problem of constructing the predetermined response of the damper with a specific displacement pattern of the piston in the damper for efficient damping of a given load is solved. The MR fluid in the damper is modeled as a Bingham phase change material with time-dependent yield stress offering continuously variable resistance to the flow in the piston to achieve the required specific displacement pattern. The governing equations are solved for any time history of the dimensionless yield stress of the fluid which in turn is determined from the imposed response of the damper. Analytical tools developed can be used in optimizing damper performance. The application of the method to resonance mitigation is illustrated. © 2021 Institute of Electrical and Electronics Engineers Inc.. All rights reserved.